2020
DOI: 10.1186/s13550-020-00627-z
|View full text |Cite
|
Sign up to set email alerts
|

Visual and quantitative evaluation of [18F]FES and [18F]FDHT PET in patients with metastatic breast cancer: an interobserver variability study

Abstract: Purpose: Correct identification of tumour receptor status is important for treatment decisions in breast cancer. [ 18 F]FES PET and [ 18 F]FDHT PET allow non-invasive assessment of the oestrogen (ER) and androgen receptor (AR) status of individual lesions within a patient. Despite standardised analysis techniques, interobserver variability can significantly affect the interpretation of PET results and thus clinical applicability. The purpose of this study was to determine visual and quantitative interobserver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Concerning the quantitative analysis of FES, no validated cutoff for FES PET in gynaecological tumors in known in literature. However, an optimal cutoff is suggested in breast cancer (SUV max of 1.54 for FES PET), which is in line with the results of our visual and quantitative assessment [18,26,27].…”
Section: Figure 3: Correlation Of Fes Positive and Negative Tumour Losupporting
confidence: 87%
“…Concerning the quantitative analysis of FES, no validated cutoff for FES PET in gynaecological tumors in known in literature. However, an optimal cutoff is suggested in breast cancer (SUV max of 1.54 for FES PET), which is in line with the results of our visual and quantitative assessment [18,26,27].…”
Section: Figure 3: Correlation Of Fes Positive and Negative Tumour Losupporting
confidence: 87%
“…[ 18 F]-FES-PET/CT enables the visualization of ER expression, with [ 18 F]-FES behaving very similar to estradiol [ 77 ]. A large prospective cohort study of 90 BC patients with first recurrence/metastatic disease and preliminary results from a prospective study in 10 ER+ MBC patients showed an excellent inter-observer agreement for [ 18 F]-FES uptake (0.90 and 0.98, respectively) [ 22 ••, 78 ]. Although limited data about repeatability and reproducibility are available, a recent guideline paper does provide recommendations regarding standardization of scanning time, control of pre-analytical factors that influence [ 18 F]-FES uptake (such as discontinuation of estrogen receptor degraders > 5 weeks prior to scanning), visual analysis, and quantification of [ 18 F]-FES uptake [ 77 ].…”
Section: Development Stages Of [ 18 F]-fes-pet/ctmentioning
confidence: 99%
“…The PET response assessment approach for bone metastases in prostate cancer using PSMA PET may be extended to other targeted PET tracers, such as 18 F-NaF and 18 F-FDHT in prostate cancer, 18 F-FES in breast cancer and 18 F-FDG and 68 Gafibroblast activation protein inhibitors ( 68 Ga-FAPI) in a multitude of cancer types (94,(99)(100)(101)(102).…”
Section: Prostate Cancermentioning
confidence: 99%